The Effect of IL-35 on the Expression of Nasal Epithelial-Derived Proinflammatory Cytokines - Mingrong Nie; Qingxiang Zeng; Luo Xi; Yiquan Tang; Renzhong Luo; Wenlong Liu (Mediators of Inflammation)
Background. Airway epithelium plays an important role during the development of allergic rhinitis (AR), which is characterized by production of thymic stromal lymphopoietin (TSLP), interleukin 33 (IL-33), and interleukin 25 (IL-25). IL-35, mainly expressed by Treg cells, have negative regulation in Th2, Th17, and ILC2 inflammation. However, the effect of IL-35 on human nasal epithelial cells (HNECs) especially the secretion of nasal epithelial-derived proinflammatory cytokines as well as the possible mechanism is still unclear. Methods. HNECs were cultured and stimulated by various stimulators. The expression of IL-33, IL-25, TSLP, eotaxin-1, eotaxin-2, and eotaxin-3 from supernatant was measured using real-time reverse transcription-polymerase chain reaction (RT-PCR) and enzyme-linked immunosorbent assay (ELISA). AR mice were developed to verify the effect of IL-35 on nasal epithelial cells in vivo. Results. After Poly I:C stimulation, IL-35 inhibited the production of IL-25, and TSLP from HNECs increased significantly compared with baseline levels (P<0.05). After Dermatophagoides pteronyssinus or Aspergillus fumigatus stimulation, IL-35 inhibited the production of IL-25, IL-33, and TSLP from HNECs increased significantly compared with baseline levels (P<0.05). After Dermatophagoides pteronyssinus, IL-35 inhibited the production of eotaxin-1, eotaxin-2, and eotaxin-3 released from HNECs increased significantly compared with baseline levels (P<0.05). Similarly, IL-35-treated AR mice presented with decreased expression of IL-33, IL-25, TSLP, eotaxin-1, eotaxin-2, and eotaxin-3 in nasal lavage fluid. Conclusion. IL-35 suppressed both type 2 inflammation-inducing cytokines and eosinophil chemotactic factor from HNECs, suggesting the important role of IL-35 during the development of AR.